An Indian scenario on renewable and sustainable energy sources with emphasis on algae - Hemaiswarya, Shanmugam (2012)
India is the fifth largest primary energy consumer and fourth largest petroleum consumer after USA, China, and Japan. Despite the global economic crisis, India’s economy is expected to grow at 6 to 8 %/year. There is an extreme dependence on petroleum products with considerable risks and environmental issues. Petroleum-derived transport fuels are of limited availability and contribute to global warming, making renewable biofuel as the best alternative. The focus on biogas and biomass-based energy, such as bioethanol and biohydrogen, will enhance costeffectiveness and provide an opportunity for the rural community. Among all energy sources, microalgae have received, so far, more attention due to their facile adaptability to grow in the photobioreactors or open ponds, high yields, and multiple applications. Microalgae can produce a substantial amount of triacylglycerols as a storage lipid under photooxidative stress or other adverse environmental conditions. In addition to renewable biofuels, they can provide different types of highvalue bioproducts added to their advantages, such as higher photosynthetic efficiency, higher biomass production, and faster growth compared to any other energy crops. The viability of first-generation biofuels production is, however, questionable because of the conflict with food supply. In the future, biofuels should ideally create the environmental, economic, and social benefits to the communities and reflect energy efficiency so as to plan a road map for the industry to produce third-generation biofuels.